The Status of Tanzania ’ s Primary School Curriculum on Environmental Education From 1980s-2010s - Ndeskoi, Thaudensia (Papers in Education and Development, 2016)
This paper reports on the historical assessment of the status of Tanzania ' s primary school curriculum in addressing environmental issues. The study covers a period of 30 years of integrating environmental education (EE) in school subjects, focusing on the extent of coverage, nature and organization of the content, teaching approaches and methods as well as relevance of the content in addressing environmental issues. This period witnessed heightened interest and public concern on EE, specifically in policy formulation hence the integration of the subject matter in the school syllabus. The study employed the mixed methods research approach to collect data. Purposive and simple random sampling were used to select heads of schools, teachers and standard VII pupils. The findings indicate that EE themes are incorporated in all school subjects through the multidisciplinary approach. Further, the content was mostly covered in Geography with a high percentage of topics 78.6% (1980-1989), 80.8% (1990-1999) and 81.3% (2000-2009), respectively. On the nature and organization of the content, the findings indicate that topics pertaining to EE were starting to be gradually introduced in the school curriculum organized around key learning areas. Also, the findings indicate that the teaching-learning approach used was predominantly the non-participatory lecture method. Furthermore, it was found that EE was seemingly irrelevant in addressing local environmental issues. To realize the critical role of EE in creating informed citizens, this study recommends that teachers should be trained in EE. The study further recommends an immediate review of Tanzania ' s primary school curriculum to include adequate, relevant and practical EE content. Therefore, it argues for the design of a curriculum oriented to solving problems as a suitable approach to the provision of EE. Keywords: Curriculum change, multidisciplinary, environnemental problems, syllabus, policy.